2017
DOI: 10.1038/s41598-017-01951-6
|View full text |Cite
|
Sign up to set email alerts
|

Stapled BIG3 helical peptide ERAP potentiates anti-tumour activity for breast cancer therapeutics

Abstract: Estradiol (E2) and the oestrogen receptor-alpha (ERα) signalling pathway play pivotal roles in the proliferative activity of breast cancer cells. Recent findings show that the brefeldin A-inhibited guanine nucleotide-exchange protein 3-prohibitin 2 (BIG3-PHB2) complex plays a crucial role in E2/ERα signalling modulation in breast cancer cells. Moreover, specific inhibition of the BIG3-PHB2 interaction using the ERα activity-regulator synthetic peptide (ERAP: 165–177 amino acids), derived from α-helical BIG3 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Phosphorylated PHB2 translocates to nuclear ERα and plasma membrane-type ERα in an E2-dependent manner, resulting in multiple suppression of E2-dependent transcriptional activity and membrane-type ERα-mediated nongenomic signaling (various phosphorylation cascades) in ERα-positive breast cancer [ 89 , 95 , 96 ]. Similar findings have also been reported for orthotopic breast cancer xenografts in nude mice [ 88 , 89 , 97 ]. The most notable aspects of this therapeutic strategy are that (1) PHB2 reactivated by ERAP suppresses various E2-ERα signaling networks, which are responsible for resistance to endocrine therapy, and (2) ERAP has antitumor effect on endocrine-resistant breast cancer xenografts [ 89 ].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Phosphorylated PHB2 translocates to nuclear ERα and plasma membrane-type ERα in an E2-dependent manner, resulting in multiple suppression of E2-dependent transcriptional activity and membrane-type ERα-mediated nongenomic signaling (various phosphorylation cascades) in ERα-positive breast cancer [ 89 , 95 , 96 ]. Similar findings have also been reported for orthotopic breast cancer xenografts in nude mice [ 88 , 89 , 97 ]. The most notable aspects of this therapeutic strategy are that (1) PHB2 reactivated by ERAP suppresses various E2-ERα signaling networks, which are responsible for resistance to endocrine therapy, and (2) ERAP has antitumor effect on endocrine-resistant breast cancer xenografts [ 89 ].…”
Section: Introductionsupporting
confidence: 88%
“…Considering its clinical use, it is essential to improve the proteolytic stability of ERAP to better maintain its inhibitory activity. Focusing on the fact that the relevant amino acid sequences of ERAP form an alpha-helix structure, we developed chemically modified ERAP (hereafter referred to as stapled ERAP: stERAP) via cross-linking of specific amino acids, with amino acids essential for BIG3-PHB2 interactions (Gln165, Asp169, and Gln173) spatially arranged at appropriate positions [ 97 ]. stERAP led to enhanced stabilization of the alpha-helical structure, potential protease resistance, and enhanced cell permeability, without the membrane-permeable polyarginine sequence of conventional ERAP [ 97 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, inhibition of the interaction of BIG3-PHB2 is a feasible strategy in estrogen-dependent cancer therapy. In fact, researchers isolated the stable ERα activity-regulator synthetic peptide (ERAP: 165-177 amino acids), a short peptide derived from α-helical BIG3 sequence that specifically binds to PHB2 and competitively prevents the BIG3/PHB2 interaction, and then showed that ERAP promotes PHB2/REA complex nuclear translocation and suppresses cancer cell proliferation in vitro and in vivo 133 . Moreover, PHB2 released from the BIG3-PHB2 complex by ERAP treatment reduces phosphorylation levels of AKT and MAPK, resulting in significant suppression of proliferation in ERα-positive breast cancer cells.…”
Section: Value Of Phb1 and Phb2 As Therapeutic Targets In Cancer Treamentioning
confidence: 99%